Crash Proof 2.0 : How to Profit From the Economic Collapse. - Schiff, Peter D. (John Wiley & Sons, 2011)
A fully updated follow-up to Peter Schiff's bestselling financial survival guide-Crash Proof, which described the economy as a house of cards on the verge of collapse, with over 80 pages of new materialThe economic and monetary disaster which seasoned prognosticator Peter Schiff predicted is no longer hypothetical-it is here today. And nobody understands what to do in this situation better than the man who saw it coming. For more than a decade, Schiff has not only observed the economy, but also helped his clients restructure their portfolios to reflect his outlook. What he sees today is a nati.